Developing of X65 steel coils making at Steckel mill using thermo-mechanical control process - Kurpe Oleksandr; Kukhar Volodymyr; Klimov Eduard; Chernenko Serhii; Prysiazhnyi Andrii (E3S Web of Conferences, 2021)
The process of thermo-mechanically controlled rolling in the conditions of Steckel mill of Ferriera Valsider plant was developed for the first time for hot-rolled coils in the sizes of 12 mm × 1510 mm from steel of X65 grade for further production of electric welded pipes according to the API-5L standard. The developed process provides carrying out of the roughing-rolling in two stages to facilitating the forming of a smaller austenite grain and therefore more dispersed and homogeneous inherited ferrite structure in the finished rolled product. At the implementation of the process, the holddown of the temperature at the desired level at 1780 Steckel rolling mill has been carried out by adjusting the number of burners in furnace coilers. The process of controlled air cooling of rolled coils to a temperature of 400°C after winding in the developed technology for Steckel’s mill condition of Ferriera Valsider plant is applied for the first time that allowed to reduce the thickness of the air scale layer and to improve the surface quality. The performed research has been allowed to evaluate the feasibility of the operating equipment and to determine the possibility of coils fabrication related to the nowadays world requirements and satisfied to the demand of European electricwelded pipes manufacturers.